Estimasi Tutupan Vegetasi menggunakan Normalized Difference Vegetation Index (NDVI) dan Keanekaragaman Jenis Pohon di sekitar Kawasan Ekosistem Leuser: Estimating Vegetation Cover using Normalized Difference Vegetation Index (NDVI) and Tree Species Diversity around Leuser Ecosystem Area - Hartoyo, Adisti Permatasari Putri; Sunkar, Arzyana; Hidayati, Syafitri; Istomo (Jurnal Silva Tropika, 2026)
ABSTRACT Leuser Ecosystem Area (LEA) is an essential tropical forest ecosystem with an expansive approximately 2,6 Mha. Baseline data of tree species diversity and structure around LEA is limited, whereas vegetation cover as a portion of forest monitoring in GLNP still needs to be considered. The objectives of this study were 1) to estimate vegetation cover changes in LEA in 2016, 2020, and 2021 and 2) to analyze vegetation composition and structure in the natural forests (NF) of GLNP, as well as in the agroforestry system (AF) of Mude Nosar Village, Central Aceh Province where the parts of LEA. The methods used were the Normalized Different Vegetation Index (NDVI) for vegetation cover estimation and vegetation analysis in both locations. NDVI analysis resulted in 5 classes of vegetation cover in LEA, to be specific non-vegetation (class 1), very low dense vegetation (class 2), low dense vegetation (class 3), moderately dense vegetation (class 4), and highly dense vegetation (class 5). LEA vegetation cover in 2016, 2020, and 2021 is dominated by class 5 (highly dense vegetation). The most frequent seedling, sapling, pole, and tree species that grew in NF of GLNP in order were Geseng tanduk (Quercus sp.), Geseng minyak (Lithocarpus lucidus), Geseng pagar anak (Lithocarpus sp.), and Geseng batu (Lithocarpus conocarpus). The dominant species in AF were rumput kerbau (Paspalum conjugatum) at the understory and seedling level, coffee (Coffea arabica) at the sapling level, lamtoro (Leucaena leucocephala) at the pole and tree level. Tree structures in the NF of GLNP are reverse J-curves, while in AF of Mude Nosar Village are not fully reverse J-curves. The success of AF depends on considering tree species composition and structure, along with the specific needs and goals of the landowners. Consequently, enrichment planting in AF is necessary for biodiversity improvement.   Keywords: agroforestry, Gunung Leuser National Park, Mude Nosar Village, species composition, tree structure         ABSTRAK Kawasan Ekosistem Leuser (KEL) merupakan ekosistem hutan tropis yang penting dengan luas sekitar 2,6 juta hektar. Data dasar mengenai keanekaragaman dan struktur spesies pohon di sekitar KEL masih terbatas, sementara tutupan vegetasi sebagai bagian dari pemantauan hutan di Taman Nasional Gunung Leuser (TNGL) masih perlu diperhatikan. Tujuan penelitian ini adalah 1) memperkirakan perubahan tutupan vegetasi di KEL pada tahun 2016, 2020, dan 2021 serta 2) menganalisis komposisi dan struktur vegetasi di hutan alam (NF) TNGL serta sistem agroforestri (AF) di Desa Mude Nosar, Kabupaten Aceh Tengah, yang merupakan bagian dari KEL. Metode yang digunakan meliputi indeks vegetasi berbasis Normalized Difference Vegetation Index (NDVI) untuk estimasi tutupan vegetasi dan analisis vegetasi di kedua lokasi. Analisis NDVI menghasilkan lima kelas tutupan vegetasi di KEL, yaitu tanpa vegetasi (kelas 1), vegetasi sangat jarang (kelas 2), vegetasi jarang (kelas 3), vegetasi sedang (kelas 4), dan vegetasi sangat rapat (kelas 5). Tutupan vegetasi KEL pada tahun 2016, 2020, dan 2021 didominasi oleh kelas 5 (vegetasi sangat rapat). Spesies yang paling sering ditemukan pada tingkat semai, pancang, tiang, dan pohon di NF TNGL secara berurutan adalah geseng tanduk (Quercus sp.), geseng minyak (Lithocarpus lucidus), geseng pagar anak (Lithocarpus sp.), dan geseng batu (Lithocarpus conocarpus). Spesies dominan di AF adalah rumput kerbau (Paspalum conjugatum) pada tingkat bawah dan semai, kopi (Coffea arabica) pada tingkat pancang, serta lamtoro (Leucaena leucocephala) pada tingkat tiang dan pohon. Struktur pohon di NF TNGL mengikuti pola kurva J-terbalik, sementara di AF Desa Mude Nosar tidak sepenuhnya mengikuti pola J-terbalik. Keberhasilan AF bergantung pada pertimbangan komposisi dan struktur spesies pohon, serta kebutuhan dan tujuan pengelola lahan. Oleh karena itu, penanaman pengayaan dalam sistem AF diperlukan untuk meningkatkan keanekaragaman hayati.   Kata kunci: agroforestri, Desa Mude Nosar, komposisi spesies, struktur pohon, Taman Nasional Gunung Leuser